Effects of emergency situations on Filipino older persons - Artajo, Arthur B.
This study looked into the effects of emergency situation on Filipino older persons. Specifically it documented these effects in terms of anxiety and worry for the unknown and financial need consequences and on their fear for disability and fear for death.The data were gathered using the active participant-observation method and interviews. Chart review was also done for the years 1997 and 1998 in order to graph the pattern of the older persons' emergency situations commonly experienced by older persons who utilized the acute care unit of the Philippine General Hospital Department of Emergency Medical Services. The cases observed and the effects of emergency situations on older persons were observed, noted down and documented by the investigator personally.Review of literature cited the changing trend of demography where more older persons continue to use emergency health care services because of a longer span of life. They have special needs which will pose challenges to the health care workers. Modern biomedicine and biotechnology have increased the life span of older people; hence there are more old people using health care institutions including emergency care services. Emergency situations that are common to older persons are also described. With pathophysiologic condition, older persons are more demanding to be attended to at once because of the fear.Being old and in a state of emergency situations have propelled social scientists to conduct in depth studies on their behavior and reaction to illness. Persons accompanying older persons in emergency care services play a significant role in assuaging fears and anxieties. Filipinos because of their strong family linkages buffer many of the older persons' fears and anxieties when they are present in the emerging room as companions or watchers.Through participant observation, more older people utilized the Emergency care services during the afternoon shifts between 2:30 p.m. to 11:00 p.m. It was not always easy to interview then because of the difficulty in hearing for some of them. Those who came at dawn were more anxious and had more manifestations of fear of disability and fear of death.A serendipity surfaced that these older people when in emergency situations utilized coping strategies to buffer the intensity of their anxiety, worry and fear. This was interestingly noted so that although coping strategies were not part of the study, these are included in the findings as serendipitous data. With these data, their coping strategies in nominal data were paired with another set of nominal form on the emergency situation effects on older persons.At X? value of 9.49 which is significant at p.05 level of confidence, there is a relationship or association between the effects of emergency situations on older persons and the coping strategies they used. Specifically this means, that the more they resort to spiritual, social support and professional help and attention, the lesser is the impact of the effect of emergency situations on them.The study concludes with the recommendation that older persons should be given a section in the ER where they can have less stressors brought about by the presence of other patients in life-threatening situations. A call is also made to have training programs to enhance nurses' attitudes and skills to care for older persons in emergency situations.Older persons by nature of their physiologic and psychologic status during emergency situations need special type of care. They are delicate and sensitive and need utmost reassurance more than the ordinary normal adult patient.